Energy Storage Devices - Taha Demirkan, M.; Attia, Adel (IntechOpen, 2019)
Energy storage will be a very important part of the near future, and its effectiveness will be crucial for most future technologies. Energy can be stored in several different ways and these differ in terms of the type and the conversion method of the energy. Among those methods; chemical, mechanical, and thermal energy storage are some of the most favorable methods for containing energy. Current energy storage devices are still far from meeting the demands of new technological developments. Therefore, much effort has been put to improving the performance of different types of energy storage technologies in the last few decades.